Inventory policy for the vaccine of a new pandemic - Pinarbasi, Aysun; Vizvari, Bela (Pergamon-Elsevier Science Ltd, 2025)
The COVID-19 pandemic underscored that vaccine inventory management differs fundamentally from conventional production-related inventory problems. In this context, ensuring supply reliability takes precedence over cost minimization. This paper applies the Hungarian inventory model to determine the optimal initial vaccine stock based on a predefined probability of avoiding shortages. Unlike traditional models, this approach incorporates the non-linear dynamics of vaccine uptake, where the population's willingness to be vaccinated follows a sigmoid time function. The vaccine stocking scenario is treated as a single-period inventory problem. Simulations are conducted for three countries-Denmark, Hungary, and Mexico-each representing different levels of public willingness to receive vaccines. The numerical results demonstrate that the target probability of non-shortage can be achieved under the proposed model. These findings offer valuable insights for public health authorities and policymakers in planning efficient and reliable vaccine procurement strategies under uncertainty.
Keywords: Pandemic; Vaccine; Hungarian inventory model; Upper confidence contour; Sigmoid function